Development of microstructure in high-alloy steel K390 using semi-solid forming - Opatova, K; Aisman, D; Rubesova, K; Ibrahim, K; Jenicek, S (IOP conference series. Materials Science and Engineering, 2016)
Semi-solid processing of light alloys, namely aluminium and magnesium alloys, is a widely known and well-established process. By contrast, processing of powder steels which have high levels of alloying elements is a rather new subject of research. Thixoforming of high-alloy steels entails a number of technical difficulties. If these are overcome, the method can offer a variety of benefits. First of all, the final product shape and the desired mechanical properties can be obtained using a single forming operation. Semi-solid forming can produce unusual powder steel microstructures unattainable by any other route. Generally, the microstructures, which are normally found in thixoformed steels, consist of large fractions of globular or polygonal particles of metastable austenite embedded in a carbide network. An example is the X210Cr12 steel which is often used for semi-solid processing experiments. A disadvantage of the normal microstructure configuration is the brittleness of the carbide network, in which cracks initiate and propagate, causing low energy fractures. However, there is a newly-developed mini-thixoforming route which produces microstructures with an inverted configuration. Here, the material chosen for this purpose was K390 steel, in which the content of alloying elements is up to 24%. Its microstructure which was obtained by mini- thixoforming did not contain polyhedral austenite grains but hard carbides embedded in a ductile austenitic matrix. This provided the material with improved toughness. The spaces between the austenite grains were filled with a eutectic in which chromium, molybdenum and cobalt were distributed uniformly. After the processing parameters were optimized, complexshaped demonstration products were manufactured by this route. These products showed an extraordinary compressive strength and high wear resistance, thanks to the hardness of their microstructure constituents, predominantly the carbides.